Innovating immune tolerance induction for haemophilia. (July 2016) - Batsuli, G.; Meeks, S. L.; Herzog, R. W.; Lacroix‐Desmazes, S.
Abstract : Introduction: Haemophilia A is an X‐linked bleeding disorder characterized by a deficiency of coagulation protein factor VIII (FVIII). A challenging complication of therapeutic FVIII infusions is the formation of neutralizing alloantibodies against the FVIII protein defined as inhibitors. The development of FVIII inhibitors drastically alters the quality of life of the patients and is associated with tremendous increases in morbidity as well as treatment costs. Aim: Current clinical immune tolerance induction protocols to reverse inhibitors are lengthy, costly and not effective in all patients. Prophylactic protocols to prevent inhibitor formation have not yet been developed in the clinical setting. However, there has been ample progress towards this goal in recent years in preclinical studies using animal models of haemophilia. Methods: Here, we review the mechanisms that lead to inhibitor formation against FVIII and two promising new strategies for antigen‐specific tolerance induction. Results: CD4+ T cells play an important role in the FVIII‐specific B cell response. Immune tolerance can be induced based on transplacental delivery of FVIII domains fused to Fc or on oral delivery of leaf cells from chloroplast transgenic crop plants. Conclusions: Recent literature suggests that prophylactic tolerance induction protocols for FVIII may be feasible in haemophilia A patients.